We will use the slope-intercept form, y = mx + b, that the problem asks for.
y = mx + b
m = slope
We are given slope = -4, so we have m = -4, and we can already put that slope in the equation for m.
y = -4x + b
Now we need to find b, the y-intercept.
We are given point (-2, 5), so we have an x value of -2 and a y value of -5.
We plug in -2 for x and 5 for y in y = -4x + b, and we solve fro b, the y-intercept.
y = -4x + b
5 = -4(-2) + b
5 = 8 + b
b = -3
Now that we have b = -3, we replace b with -3.
y = -4x + b
y = -4x - 3
Answer: y = -4x - 3